Environment crucial to human security - Abd Razak, Dzulkifli (2006)
THE world today is increasingly becoming insecure. But most would understand this in a narrow sense, namely in the context of national security, that is, the vulnerability of the nation state being attacked. Thus, the focus is mainly on protecting the state — its boundaries, peoples, institutions and values — from outside intrusions. Unfortunately, nowadays it is not only the state that is less secure, but also the individual. There is then an urgent need to conceptualise the notion of human security, taking into account the complex interrelated threats associated with war and genocide, and the resulting mass displacement of people. The importance of human security is underscored by the fact that about 2,8 billion are said to suffer from poverty, ill health and illiteracy as compared to about 800,000 people a year said to have lost their lives to violence per se.